Union dissolution and childlessness. New insights from sequence analysis - Rannveig Kaldager Hart (Statistics Norway, Research Department, 2015)
This study investigates how the association between union dissolution and childlessness depends on life course context. Data on union histories and fertility are taken from the Norwegian GGS. To observe union histories up to age 45, I include men and women born 1927-1962, giving a study sample of 3862 men and 3956 women. To grasp the life course context of union dissolutions, I group union histories similar in timing, occurrence and ordering of events together using sequence analysis. Union histories involving at least one dissolution are sorted into two groups: In the first group, a short first union is followed by quick repartnering, and the second union is still intact at age 45 for the majority. In this group, childlessness is low. In the second group, individuals spend more time as single before and after unions, and dissolving more than one union is common. This group displays high levels of childlessness. The association between a complex union history and childlessness is substantially and significantly stronger among men than among women. Among women, union histories involving a dissolution is more strongly linked to childlessness for the highly educated.
Keywords: J12; J13; J16; 330; Childlessness; Union dissolution; Partnership dynamics; Sequence Analysis